Kafala. On legal position of migrant workers in Gulf countries - Skowron, Radosław T. (Studia Iuridica Toruniensia, 2021)
In Polish reviews, both legal and devoted to Islam studies, the analysis of legal institutions in Arab states is still a rare phenomenon. In the meantime, the Gulf region, apart from dynamic economic growth and expanding influence in spheres of culture, media, sports or transport, has become in the last five decades a destination of one of the most numerous working migrations in history. Next to extraction of oil and gas, migrant workers are now the backbone of economies of the states forming Gulf Cooperation Council. In order to manage the influx of migrants these countries have created a system of legal regulation called, in Arab language, kafala. It is a web of labour law, citizenship law and foreigners law covering different aspects of rights and obligation of working migrants in the Gulf states. The system however has been for many years castigated by international community as suppressing human rights and employees’ dignity. The author describes historical circumstances leading to the current shape of kafala and indicates distinct features of this system in the Gulf states. An analysis of kafala from the perspective of both traditional Islam law, sharia, and international covenants, is being presented. In the conclusion the author states that kafala system in its today’s version is compatible with neither Muslim law, nor the international treaties.